Fourier-Legendre Spectral Method for the Unsteady Navier-Stokes Equations (Journal of Computational Mathematics, 1995)
Fourier-Legendre spectral approximation for the unsteady Navier-Stokes equations is analyzed. The generalized stability and convergence are proved respectively.